Role of speciality corn and their specific production technologies to enhance farmers’ income - BAJPAI, RAMAKANT; GOSWAMI, R G (Indian Farming, 2018)
Compared to field corns, specialtycorns possess additional andcharacteristic features. Their globalspread, increasing demand andpremium price make them anattractive option for the farmers inmany foreign countries includingIndia. Specialty corns are amenable tonumerous options pertaining toharvest time and various economicalproducts.